The Role of Green Zakat and Infaq Funds to Sustainability Coastal Environment - Wiwit Widhi Setiyawan; Arimbi Putri Kinanti; Herman Kurniawan; Sunardi; Rofiq Nurhadi; Nif’an Nazudi (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2026)
This study aims to conduct an in-depth and contextual exploration of the utilization of zakat and infaq funds to support environmental sustainability initiatives in coastal areas. The study employs a qualitative approach. Both primary and secondary data were utilized and cross-analysed to ensure the validity and robustness of the research findings. The findings reveal that, in its effort to contribute to Sustainable Development Goal 14 (SDG 14), Lazismu Purworejo has mobilised green zakat and infaq funds from the community to promote environmental sustainability through the planting of coastal pine (Casuarina Equisetifolia) trees along the coastal area of Keburuhan Beach. The programme has generated several significant benefits, including improving the air quality index, increasing land cover in coastal regions, fostering public awareness and environmental stewardship, and ensuring the income stability of coastal communities. The implementation of this initiative has been carried out in collaboration with relevant government institutions and other strategic partner organisations.